Mechanisms of weight loss and improved metabolism following bariatric surgery. Issue 1 (3rd September 2017) - Mulla, Christopher M.; Middelbeek, Roeland J.W.; Patti, Mary‐Elizabeth
Abstract: Bariatric surgery is increasingly recognized as one of the most effective interventions to help patients achieve significant and sustained weight loss, as well as improved metabolic and overall health. Unfortunately, the cellular and physiological mechanisms by which bariatric surgery achieves weight loss have not been fully elucidated, yet are critical to understanding the central role of the intestinal tract in whole‐body metabolism and to developing novel strategies for the treatment of obesity. In this review, we provide an overview of potential mechanisms contributing to weight loss, including effects on regulation of energy balance and both central and peripheral nervous system regulation of appetite and metabolism. Moreover, we highlight the importance of the gastrointestinal tract, including alterations in bile acid physiology, secretion of intestinally derived hormones, and the microbiome, as a potent mediator of improved metabolism in postbariatric patients.